Subterranean Campodeidae fauna from Sicily (Diplura): its biogeographical interest with the description of a new species of Plusiocampa - Sendra, Alberto; Nicolosi, Giuseppe; Amore, Elena (Zootaxa, 2019)
A description is given of a biogeographically interesting new species of Campodeidae (Diplura), Plusiocampa (Plusiocampa) tinoamorei sp. nov., a troglobiotic species found in the Sicilian Villasmundo and Scrivilleri caves. A second subterranean species already known from three caves in northwest Sicily near Palermo, Campodea (Campodea) majorica sicula Condé, 1957, also was studied. Both species were characterized with SEM. Each species belongs to a different monophyletic group: Plusiocampa s. str., with thoracic medial posterior macrosetae, and the group related to Campodea (Campodea) grassi Silvestri, 1912. Both groups are widely distributed on almost all of the large western Mediterranean islands. Nevertheless, although these two monophyletic groups have a different origin both could be dispersed via land connections between the mainland and the islands during the Messinian Age. This new discovery shows the great value of Sicilian caves that hold species with unique features and of high biogeographic significance.